OPC TECHNOLOGY AS AN AUTOMATED SYSTEMS INTEGRATION TOOL - Karatayev, Aibek Ashatovich; Palshin, Vasiliy Pavlovich; Yarmuhamedova, Zauresh Mukashevna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper features the application of the OPC technology in automated systems. It gives an insight into the considered technology and provides the prospects of the OPC technology development.